The effect of anisotropic microstructure on the crack growth and fatigue overload behaviour of ultrafine-grained nickel. (1st February 2020) - Zhang, W.; Simpson, C.A.; Leitner, T.; Zhang, X.; Pippan, R.; Withers, P.J.
Abstract: Changes in crack growth rate associated with overload events during fatigue are poorly understood, especially for materials with anisotropic microstructures. Here overload fatigue tests are reported for compact tension samples cut in two different orientations from high pressure torsion disc samples. During growth the crack planes reoriented either slightly, or significantly, to align with the elongated grain structure leading to low, and high, levels of mixed mode fatigue loading respectively. In both cases the ultrafine grained microstructure led to macroscopically flat crack faces. The fatigue crack growth rate was around 2.4 times slower for the case with the high mode II component than for the low. A 100% overload was then introduced and synchrotron X-ray diffraction and digital image correlation (DIC) were applied in-situ to map the bulk crack-tip elastic strain field (plane strain) and surface displacement field (plane stress) respectively prior to, during and after overload. The high mode II case displayed a larger degree of retardation after overload. Residual stress and plasticity-induced crack closure were found to be the primary causes for the retardation as the crack grows into the overload plastic zone. Significant crack face contact was observed for the high mode II case along with significant levels of compressive stress transferred across the crack faces at minimum load. Compared with conventional (coarse) grain Ni, the ultrafine grained Ni is less retarded by overload, because of its relatively flatter crack path and higher yield stress and thus less plasticity and residual stress induced closure. Graphical abstract: Image, graphical abstract